Neurological Implications of Non-critically Ill Patients With Coronavirus Disease 2019 in a Fangcang Shelter Hospital in Wuhan, China - Yan, Nao; Xu, Zhipeng; Mei, Bin; Gao, Yongzhe; Lv, Dongwei; Zhang, Junjian (Frontiers in Neurology, 2020)
Background Coronavirus disease 2019 (COVID-19) is a new viral respiratory disease and has become a pandemic that is threatening global health. Fever, weakness, and dry cough are the main clinical manifestations. Less is known about neurological symptoms of non-critically ill COVID-19 patients. Objective To investigate the neurological symptoms and their incidence and implications of patients with non-critically ill COVID-19 patients. Materials and Methods This retrospective cohort study analyzed all COVID-19 patients admitted to Wuhan East-West Lake Fangcang shelter hospital. Demographic data, clinical manifestations, comorbidities, radiological data, the result of nucleic acid test, treatments were collected and analyzed. Results Among 1682 patients with confirmed non-critically ill COVID-19, 509 patients (30.3%) had neurological symptoms, including myalgia (311, 18.5%), headache (216, 12.8%), fatigue (83, 4.9%) and dizziness (15, 0.9%). 114 patients (6.8%) were the expansion of pulmonary infection according to their chest CT images and medical history. Compared with patients without neurological symptoms, patients with neurological symptoms had a significantly longer length of hospital stay、time of nucleic acid turning negative, and the mean time from onset of symptom to hospital admission (p< .05). Patients with neurological symptoms were more likely to occur the expansion of pulmonary infection compared with the patients without neurological symptoms (46/509 [9.0%] vs 68/1173 [5.8%]). Conclusions Non-critically ill COVID-19 patients commonly have neurological symptoms. Neurological symptoms reflecting nervous system injury are significantly associated with the processes of COVID-19. Early identification and aggressive treatment are particularly important for COVID-19 patients with neurological symptoms.